Public Institutions and Cultural Diplomacy. Possibilities and Challenges - Kieliszewski, Przemysław; Poprawski, Marcin (Journal of Public Governance, 2009)
The article describes problems and inconsistencies as well as possibilities and challenges of Polish cultural diplomacy. Cultural diplomacy is much more than just a promotion of culture; it is one of the key state policy tools. Culture constitutes the best medium of broader, integrative human values and a means of understanding others. It encompasses the most valuable, lasting and meaningful aspects of our lives. The symbolic culture formulates narrations which allow us to present the best characteristics of our nations and societies, universal behaviours or different attitudes, varied hierarchies of values. Culture is a laboratory of identity policies and their construction, a critical forum for negotiations and communication of values. Critical remarks and rationalizations presented in the paper concern operations in thedomain of cultural diplomacy in the Polish public sector. The article is based on one of the first qualitative studies in the field, prepared by experts, practitioners, artists and cultural managers. The authors encourage to undertake new activities in order to supply and apply systemic and transparent solutions for evaluation of public institutions which promote Polish culture abroad. Defining deficits and potentials of a complex domain that is the promotion of Polish culture and the Polish brand is only the first step.